What kind of economists do we want? - Henrekson, Magnus (Economic and business review, 2025)
We explore the challenges facing the current academic training of economists in small European countries such as Sweden. The monolithic focus on publishing in the top-five journals, which prioritizes methodological rigor over problem-driven research, is often a threat to social relevance and policy applicability. This limits pluralism, excludes many talented economists, and fails to prepare graduates for nonacademic positions. We propose a two-track model for PhD training and academic evaluation, emphasizing both traditional research and applied economic policy, tailored to the diverse needs of academia, public administration, and business. We also argue for broader evaluation criteria, enhanced interdisciplinary collaboration, and institutional reforms, including trial lectures and specialized research institutes. By diversifying incentives, we recommend a shift towards socially relevant and more inclusive education and practice in the discipline of economics.
Keywords: economic research; ekonomsko raziskovanje; employment; productivity; produktivnost; zaposlovanje